Risk of multiple myeloma is associated with polymorphisms within telomerase genes and telomere length - Campa, Daniele; Martino, Alessandro; Varkonyi, Judit; Lesueur, Fabienne; Jamroziak, Krzysztof; Landi, Stefano; Jurczyszyn, Artur; Marques, Herlander; Andersen, Vibeke; Jurado, Manuel; Brenner, Hermann; Petrini, Mario; et al. (International journal of cancer, 2015)
Compelling biological and epidemiological evidences point to a key role of genetic variants of the TERT and TERC genes in cancer development. We analyzed the genetic variability of these two gene regions using samples of 2,267 multiple myeloma (MM) cases and 2,796 healthy controls. We found that a TERT variant, rs2242652, is associated with reduced MM susceptibility (OR = 0.81; 95% CI: 0.72-0.92; p = 0.001). In addition we measured the leukocyte telomere length (LTL) in a subgroup of 140 cases who were chemotherapy-free at the time of blood donation and 468 controls, and found that MM patients had longer telomeres compared to controls (OR = 1.19; 95% CI: 0.63-2.24; ptrend = 0.01 comparing the quartile with the longest LTL versus the shortest LTL). Our data suggest the hypothesis of decreased disease risk by genetic variants that reduce the efficiency of the telomerase complex. This reduced efficiency leads to shorter telomere ends, which in turn may also be a marker of decreased MM risk.
Gesehen am 03.11.2020
Online 28 Jul 2014